Ruscheweyh-type starlike functions of complex order associated with q-difference operator - Çetinkaya, Asena (SPRINGER INTERNATIONAL PUBLISHING AG, GEWERBESTRASSE 11, CHAM, CH-6330, SWITZERLAND, 2019)
In this paper, we introduce three new subclasses of starlike functions of complex order by using Ruscheweyh-type q-differential operator. We investigate inclusion theorem, sufficient coefficient estimates, distortion bounds and radius of starlikeness for the functions belonging to these subclasses. Moreover, partial sums of these subclasses were obtained.
Keywords: q-Calculus; q-Difference Operator; Ruscheweyh Differential Operator